Implementation of Rainfall Monitoring through an Information System Based on Radar and Satellite Image Data using the Kalman Filter Method - Sugiarto; Putra, Maulana; Syaefudin, Mohamad Anwar; Rosid , Mohammad Syamsu; Handoko, Djati (Faculty of Computer Science (FILKOM) Brawijaya University, 2024)
Rainfall information is important for water resource management and disaster mitigation, so a monitoring system is needed that can provide spatial information. A rainfall monitoring information system uses radar and satellite images based on the Kalman Filter method is a website information system that aims to make it easier for users to monitor rainfall from a latitude and longitude coordinate point. The rain intensity data is in pixel colours (Red, Green, Blue) from the MAX (dBZ) product image of the EEC Weather Radar in Lampung and cloud top temperature data from the Himawari satellite. The image pixel colour data is then processed using the Kalman filter and displayed on the integrated website. The website's appearance is designed to be interactive to accommodate user customization, and the data displayed has been adapted to geographic information systems. Implementing a rainfall information system based on weather radar and satellite imagery disseminated through the website is expected to help users, both the general public and stakeholders, access real-time weather information, especially rainfall.